PENERAPAN TRANSISI PAUD KE SD UNTUK PEMENUHAN FONDASI ANAK DI KELAS I SD NEGERI 5 RAMBANG - Mayori, Evi Erisa; Lian, Bukman; Utomo, Budi (STKIP Persada Khatulistiwa Sintang, 2025)
The transition from Early Childhood Education (PAUD) to Elementary School (SD) is a crucial stage in a child’s development, involving social and emotional adjustments as well as adaptation to a more complex curriculum. This study aims to explore and understand the strategies implemented to support the PAUD–SD transition at SD Negeri 5 Rambang. The main focus of this research is on the application of effective transition strategies, which include environmental adaptation and the development of children’s social skills. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation to gain an in-depth understanding of the transition process. The findings are expected to provide insights into the importance of fulfilling the developmental foundations of children—cognitive, social, emotional, and psychomotor—and to offer practical recommendations for teachers and parents in preparing children to face more formal and complex education settings.